Field based assessment of insect pest dynamics in Egyptian clover crop within a rice-wheat cropping system (Zoo Botanica, 2025)
Egyptian clover (Trifolium alexandrinum) is an important forage crop in the rice–wheat cropping system but is vulnerable to diverse insect pests. A field-based assessment was carried out during February-March 2025 to investigate insect pest dynamics and their natural enemies under field conditions. Systematic sampling revealed that thrips were the dominant pest, total counts during 50 sweeps (mean per sweep: 7.20 to 185.72 to 14.52) increased from 360 individuals on 22.02.2025 to a high level of 9286 individuals on 25.02.2025 before falling to 726 individuals by 03.03.2025.  Aphids were the second most significant pest with a maximum of 6.80 individuals (over 50 sweeps) on February 28, 2025 (mean per sweep: 0.136), followed by a rapid decline and complete disappearance by early March. Other pest groups, including grasshoppers, field crickets, houseflies, leafhoppers, butterflies, and bluemilk weed beetles, appeared sporadically and never exceeded 5.60 individuals. Insects like rove beetles and spiders had also been recorded to be beneficial in the sampling period with a maximum of 11.60 and 5.20 individuals recorded, respectively; this was not enough to control the severity of thrips and aphid infestation. Overall, the experiment shows that thrips pressure is much stronger in the Egyptian clover as compared to aphids, and the natural enemies do not have a significant effect. It is important to note that there is need to monitor time promptly and adopt integrated pest management control approaches to reduce yield losses that may be realized in clover planting in the rice-wheat system.
Keywords: Egyptian clover; population fluctuation; thrips; aphids; natural enemies; rice-wheat system; integrated pest management